From one to many central plans: drug advertising inspections and intra-national protectionism in China - Eberhardt, Markus; Wang, Zheng; Yu, Zhihong (Elsevier, 2016)
This paper provides the first micro-level evidence for the existence and patterns of intra-national protectionism in China. We demonstrate that drug advertising inspections are used by provincial governments to discriminate against firms from outside the province. We further reveal systematic patterns in the degree of discrimination across firms: those from neighboring areas, those from regions with more economic links to the destination province, those from provinces with stronger presence in the market, and those with political ties to “allied” provincial governments are less likely to be targeted. Our findings highlight the unique politico-economic structure in China and confirm that giving local governments strong incentives to compete with each other may exacerbate the market distortions inherent in a partially reformed economy.